Photocatalytic reduction of Cr(VI) over TiO2-coated cellulose acetate monolithic structures using solar light - Belisa A. Marinho (2017)
The major drawback of TiO2 based advanced oxidation processes (AOPs) is the use of massive amounts of dispersed nanoparticles that are hard to recover after the water treatment and potentially harmful for humans due to their very small size. The stabilization of the nanoparticles in an adequate inert support is a good strategy to overcome such limitations. In the present work, the photoreduction of Cr(VI) to Cr(III), using citric acid as a hole scavenger, was performed in a tubular photoreactor packed with cellulose acetate monolithic (CAM) structures coated with TiO2-P25 thin films by a simple dip coating method and irradiated by simulated or natural solar light. Firstly, the effect of TiO2 coating layers number on the Cr(VI) photoreduction was analysed. At the optimal amount, the photoreactor provides 0.10 g of TiO2 per liter of liquid inside the reactor. The support geometry allowed a high surface-area-to-volume ratio, offering an illuminated catalyst surface area per unit of volume inside the reactor of 212 m(2) m(-3). Following, operating conditions such as pH value, citric acid concentration, irradiation source and initial Cr(VI) concentration were analysed. Several. organic species were also tested as hole scavengers. Results indicate reduction rates of 0.07 mmol(cr(VI)) m(illuminatedvolume)(-3) S-1 and a photonic efficiency of 1.9% during the reduction of 0.02 mM of Cr(VI) with 6 P25 layers and 6.9 mM of citric acid at pH 2.5 and 25 degrees C. Furthermore, the catalytic bed was reused for 10 consecutive cycles with almost no efficiency decrease after the second cycle, achieving near 100% Cr(VI) removal after 90 min.